Mutualistic Relationships between Plants and Mycorrhizal Fungi Impacts on Ecosystem Functioning: A Review - Reddy, Gurrala Sai Vamsi; Bokka, Sai Krishna Reddy; Chellem, Sushma Raj; Kalpana, Kavuri; Indrani, Kopparthi; Bindu, Tallam Pavani Lakshmi Hima; Navya, Danaboyena Sri (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Mycorrhizal fungi form mutualistic relationships with the majority of terrestrial plants, influencing nutrient uptake, soil structure, plant growth, and ecosystem functioning. The diverse types of mycorrhizal associations, including arbuscular mycorrhizae (AM), ectomycorrhizae (ECM), ericoid mycorrhizae (ERM), and orchid mycorrhizae (ORM), each contributing uniquely to plant health and soil ecosystems. Mechanisms of interaction, such as fungal colonization, nutrient exchange, signaling pathways, and carbon allocation, underscore the complexity and significance of these symbioses. Mycorrhizal fungi enhance ecosystem functioning by improving nutrient cycling-particularly the carbon, nitrogen, and phosphorus cycles-stabilizing soils, and increasing plant stress tolerance. Case studies in agricultural systems demonstrate how mycorrhizal inoculation can improve crop yields and soil health, while natural ecosystems illustrate their role in supporting biodiversity and resilience. In restoration ecology, mycorrhizal fungi aid in the recovery of degraded lands, enhancing plant establishment and soil stability. Urban and industrial landscapes also benefit from mycorrhizal associations, which support vegetation in challenging environments. Despite advancements, significant knowledge gaps and technological limitations persist, particularly regarding the ecological specificity of mycorrhizal fungi and their interactions within the soil microbiome. Addressing these challenges requires interdisciplinary approaches and integrating mycorrhizal research into policy and management practices. Such integration can enhance sustainable agricultural practices, promote biodiversity conservation, and mitigate climate change impacts. Future research should focus on advancing molecular techniques, improving in situ study methods, and fostering collaboration across scientific disciplines to fully harness the ecological and agricultural potential of mycorrhizal fungi. This comprehensive understanding of plant-mycorrhizal interactions is crucial for developing strategies to sustain healthy ecosystems and improve agricultural productivity in the face of environmental challenges.